Regional development paradigm: geographical aspects of tourist and recreational destinations - Boretska, N.; Krapivina, G.; Marchenko, I. (Економічний вісник Донбасу, 2025)
Tourism and recreation are a multidisciplinary phenomenon that accumulates natural, socio-cultural, economic and environmental factors, integrating them in a specific geographical space. Geographical research of tourist and recreational destinations is a scientific basis for spatial planning, the formation of tourist clusters, strategic positioning of regions and the implementation of the concept of their sustainable development, which consists in substantiating an integrated approach to clustering and typification of destinations in Ukraine based on geographical aspects and a mix model of cluster analysis, which are supplemented by a model of the life cycle of destinations taking into account external and internal factors of the post-war reconstruction of the country. Rethinking the geographical aspects of the development of destinations for the economic, social and cultural recovery of Ukraine based on the search for an effective cluster model for the development of the tourist and recreational complex and the principles of public-private partnership. Therefore, the analysis of the geographical typology of destinations in the study is based on taking into account the spatial, natural-geographical and landscape characteristics of the territories. Spatial types of destination organization reflect the degree of compactness, interconnection and concentration of tourist functions within a specific territory. Outside a specific destination, external factors are formed and developed, which are the result of global, national or interregional processes and act as catalysts or constraints that shape the general environment for the functioning of the tourist and recreational space. They set macro conditions: geopolitical stability, investment climate, political will to support private-public partnership, international aid, etc. The ability of territorial communities, business and authorities to use external incentives; adapt to challenges (in particular post-war ones) and mobilize available resources are internal factors and the driving force of cluster formation. The classification of clustering models of tourist and recreational destinations allows to form a systemic basis for their typification and strategic management of development, and the use of a cluster mix model, which combines hierarchical clustering, k-means algorithms, density clustering methods (DBSCAN), as well as network approaches (Louvain, Girvan–Newman), provides a flexible, comprehensive and adaptive toolkit for analyzing the structural, functional and spatial features of tourist and recreational territories. Туризм та рекреація – це мультидисциплінарне явище, яке акумулює природні, соціально-культурні, економічні та екологічні фактори, інтегруючи їх у певному географічному просторі. Географічні дослідження туристично-рекреаційних дестинацій є науковою основою просторового планування, формування туристичних кластерів, стратегічного позиціонування регіонів та реалізації концепції їх сталого розвитку, що полягає в обґрунтуванні комплексного підходу до кластеризації та типізації дестинацій в Україні на основі географічних аспектів та мікс-моделі кластерного аналізу, які доповнюються моделлю життєвого циклу дестинацій з урахуванням зовнішніх та внутрішніх факторів повоєнної відбудови країни. Переосмислення географічних аспектів розвитку дестинацій для економічного, соціального та культурного відновлення України базується на пошуку ефективної кластерної моделі розвитку туристично-рекреаційного комплексу та принципах державно-приватного партнерства. Тому аналіз географічної типології дестинацій у дослідженні базується на врахуванні просторових, природно-географічних та ландшафтних характеристик територій. Просторові типи організації дестинацій відображають ступінь компактності, взаємозв'язку та концентрації туристичних функцій у межах певної території. Поза межами конкретної дестинації формуються та розвиваються зовнішні фактори, які є результатом глобальних, національних або міжрегіональних процесів і виступають каталізаторами або обмеженнями, що формують загальне середовище функціонування туристично-рекреаційного простору. Вони задають макроумови: геополітичну стабільність, інвестиційний клімат, політичну волю до підтримки приватно-державного партнерства, міжнародну допомогу тощо. Здатність територіальних громад, бізнесу та влади використовувати зовнішні стимули, адаптуватися до викликів (зокрема, повоєнних) та мобілізувати наявні ресурси є внутрішніми факторами та рушійною силою формування кластерів. Класифікація моделей кластеризації туристично-рекреаційних дестинацій дозволяє сформувати системну основу для їх типізації та стратегічного управління розвитком, а використання моделі кластерного міксу, яка поєднує ієрархічну кластеризацію, алгоритми k-середніх, методи кластеризації за щільністю (DBSCAN), а також мережеві підходи (Лувен, Гірван-Ньюмен), забезпечує гнучкий, комплексний та адаптивний інструментарій для аналізу структурних, функціональних та просторових особливостей туристично-рекреаційних територій.